Atlas of the forest sector in Belarus - Gerasimov, Yuri; Karjalainen, Timo (Finnish Forest Research Institute, 2010)
This atlas is a collection of maps with a short description of the current situation of the forest sector inBelarus including regions of Brest, Gomel, Grodno, Minsk, Mogilev, and Vitebsk. The cartographicinformation is grouped in the following way: forest resources, silviculture, wood harvesting, productionand the most important producers of wood-based products (sawnwood, plywood, wood-based panels,pulp, paper, paperboard), potential of energy wood, as well as producers of forest-related machinery,wood pellets and briquettes, forest education, and research institutions. This review serves the informationneeds of different stakeholders and those interested in the forest sector in Belarus.
Keywords: Valko-Venäjä; bioenergia; metsäpolitiikka; metsäteollisuus; metsävarat; puunkorjuu; Belarus; bioenergy; forest industry; forest policy; forest resources; wood harvesting